EFEKTIFITAS GAMIFIKASI DALAM PEMBELAJARAN MATEMATIKA - Nurjannah Nurjannah; Andi Baso Kaswar; Eman Wahyudi Kasim (JURNAL MathEdu (Mathematic Education Journal), 2021)
This research was an experimental research using True Experimental Design with pretest and posttest. This study aims to see the effectiveness of the use of gamification in mathematics learning. The gamification referred to in this study are Kahoot! and Quizizz. This research was conducted at SMP Negeri 2 Kahu. The samples in this study were 27 students of class VIIIB. The data analysis technique was performed using paired sample t-test. However, before that, a normality test was carried out on the research data. The results of the normality test show that the Asymp Sig. (2-tailed) of 0.200 greater than 0.05, which means that the data is normally distributed. While the results of the paired sample t-test obtained a significance value of 0.000 where this value is less than 0.05. So, based on the rules of decision making, it is found that there are differences in learning outcomes before and after gamification. In other words, giving gamification is effective in learning mathematics.